Factors associated with the use and composition of two-drug regimens in a large single-centre HIV cohort. (22nd July 2021) - de Lazzari, Elisa; Gonzalez-Cordon, Ana; Inciarte, Alexy; Ugarte, Ainoa; de la Mora, Lorena; Martinez-Rebollar, Maria; Laguno, Montserrat; Ambrosioni, Juan; Torres, Berta; Mallolas, Josep; Blanco, Jose L; Miro, Jose M; et al.
Abstract: Objectives: We aimed to assess the clinical characteristics associated with the use of two-drug regimens (2DRs) and the factors associated with specific antiretrovirals in 2DRs in a large single-centre HIV cohort. Methods: Retrospective analysis of demographics, HIV characteristics and AIDS events, antiretroviral prescription, virological failure and genotypic resistance testing, and laboratory results from all adult people with HIV (PWH) prospectively followed at the Hospital Clinic of Barcelona who were receiving a 3DR or a 2DR in January 2020. We assessed factors associated with the probability of receiving 2DRs relative to three-drug regimens (3DRs) using a logistic regression model, controlling for age, sex and year of HIV diagnosis. The same methodology was applied to identify factors associated with the prescription of integrase inhibitor-based regimens or PI-based regimens among PWH receiving 2DRs. Results: There were 3432 (88%) PWH receiving 3DRs and 463 (12%) receiving 2DRs. In the final adjusted model, ≥2 previous virological failures, previous resistance mutations, previous AIDS diagnosis, longer time on current regimen, higher total cholesterol or triglycerides and lower baseline haemoglobin were independent factors associated with 2DRs. The majority of 2DRs included an integrase inhibitor or/and a PI. We identified independent factors associated with the inclusion of integrase inhibitors (lower HDL cholesterol) or PIs (prior AIDS, prior genotypic resistance mutations and lower CD4/CD8 ratio) in the 2DR. Conclusions: In this large single-centre HIV cohort, a worse cardiometabolic status or more archived resistance were key factors associated with inclusion of integrase inhibitors or PIs, respectively, in 2DRs.